Neural Networks in Cybersecurity (American Journal of Public Diplomacy and International Studies (2993-2157), 2023)
Deep learning is a part of machine learning based on neural networks. Nowadays, everyone has heard about neural networks, and maybe not everyone knows what it is and what it does, but the name itself is familiar to everyone.